Textbook on torts - Jones, Michael A. (Oxford University Press, 2002)
This is the new edition of the well-established and widely recommended textbook on the law of torts by Professor Michael Jones. The eighth edition offers concise, yet comprehensive and accurate coverage and provides detailed analysis that encourages an in-depth understanding of this core area of law